If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 + -42y + -1y = 0 Combine like terms: -42y + -1y = -43y 70 + -43y = 0 Solving 70 + -43y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + -43y = 0 + -70 Combine like terms: 70 + -70 = 0 0 + -43y = 0 + -70 -43y = 0 + -70 Combine like terms: 0 + -70 = -70 -43y = -70 Divide each side by '-43'. y = 1.627906977 Simplifying y = 1.627906977
| -12=4-n | | 5e+15=4e+8 | | 3x+3y=102 | | 1x/9 | | 1/2(2x-4)=2(4-6x) | | y=7500+19x | | 7b+13=3b-17 | | 18-6m=5-4m | | 3a+5b-7b= | | n+n+1+n+2=27 | | 2(w-4)=8w+10 | | 6/7=x/10.5 | | 27x-3=51 | | 2a+8=3a-1 | | 51x-3=27 | | 5(x-2)=5x-11 | | 2(x+10)+3x=85 | | 51x-27=3 | | 32-5x=50-3x | | 5x+2(17-4x)=4 | | 3.2-0.5x=5-0.3x | | 4b+25+3b=-50 | | -11p+20p-6p-8p-p=16 | | -6(2x-1)=25 | | 3/4n-8=-17 | | 11/20-5/20= | | (4b+6)(6-4)= | | -15t+14t=7 | | x+x+1+x+2+x+3=-22 | | 3(2-2x)=2(4+5x) | | 0.8(x-4)=2(0.4x+1.6) | | 59=8y-9 |